Diversity and honey properties of stingless bees from meliponiculture in East and North Kalimantan, Indonesia - SYAFRIZAL; RICO RAMADHAN; IRAWAN WIJAYA KUSUMA; SAAT EGRA; KUNIYOSHI SHIMIZU; MAMORU KANZAKI; Enos Tangkearung (Society for Indonesian Biodiversity, 2020)
Abstract. Syafrizal, Ramadhan R, Kusuma IW, Egra S, Shimizu K, Kanzaki M, Arung ET. 2020. Diversity and honey properties of stingless bees from meliponiculture in East and North Kalimantan, Indonesia. Biodiversitas 21: 4623-4630. Kalimantan Island in Indonesia is covered by tropical rain forests that are rich in biodiversity. Species, include a stingless bee (Trigona spp.). Recently, stingless bee beekeeping (Meliponiculture) in this region has become popular because the honey has a unique taste, a mix of sweet, sour, and bitter which is highly valued. The objective of this study was to determine the diversity of stingless bee species, the number of colonies, type of hive, and honey properties such as taste, acidity, color, phytochemicals, and radical scavenging activity or antioxidant in meliponiculture in selected areas of Eastern and Northern Kalimantan, Indonesia. The area studied included Samarinda, Balikpapan, Penajam, Bontang, Sangatta, and Tarakan. The study conducted by visiting the farmers, collecting the stingless bees species and bee products (honey, propolis, and bee pollen), pH, color and taste determination, phytochemical screening, and DPPH assay. We found 12 species, with Heterotrigona itama and Tetragonula laeviceps being the main ones cultivated by people in all research areas, except Balikpapan. We counted 111 colonies of T. laeviceps and 99 of H. itama in the meliponiculture. There were three types of hive used by farmers in meliponiculture. Most of the honey tasted sweet and sour with acidity or pH ranging from 3-4, and color from dark brown to light yellow. The phytochemicals contained tannin, alkaloid, flavonoid, triterpenoid, carotenoid, coumarin, saponin, and carbohydrate. The Tetragonula sarawakensis honey was the most potent in term radical scavengers. Our findings showed that stingless bee honey contains antioxidants with phytochemicals that are very useful for human health.